Relevance of EIA in Sustainable Development with Labour Law - Putri, Vanesa Ingka; dahlia, Nelly; Warjiyati, Sri (IDFoS Indonesia, 2023)
The process of drafting legislation that concerns the livelihood of many people needs to be a careful and participatory process, the Job Creation Bill has crucial problems when viewed from the methodological aspects, paradigm and substance of regulation in the policy field of over-regulated and over-lapping issues that occur in the regulation of fields related to development and investment will not be resolved because the Job Creation Bill requires around 500 derivative regulations so that it has the potential to create a complex hyper-regulated. Realising that there is a need to create a conducive investment climate to realise development, it should not ignore the principle of sustainable development. The purpose of this research was to find out the relevance of EIA in sustainable development in Indonesia where the problem with the current job creation law is suspected of changing the function of EIA which was previously one of the licensing requirements to something whose function is no longer important or only needs to increase the problem with the concept of regulation regarding the environment which was previously regulated by Law Number 32 of 2009 concerning Environmental Protection and Management (UPPLH) using a licensing-based approach. This research used normative or doctrinal research methods.